Smart Calculator 3.0 / Mahfuzah Mahayadin ... [et al.]. - Mahayadin, Mahfuzah; Mohamed, Nadiah; Mohd Ruslan, Siti Zaharah; Ismail, Norul Fadhilah; Othman, Norlida; Yaacob, Nurul Aityqah; Andu, Yusrina; Razalli, Nur Anis Fatihah; Jaafar, Nor Fadhlin; Ahmad, Mardiana (Universiti Teknologi MARA, Negeri Sembilan, 2024)
The "Smart Calculator 3.0" workshop was held on 20th to 24th November 2023. The aimed was to explore advanced functionalities and applications of scientific calculators in learning mathematics and statistics. The program provided participants with hands-on experience and insights into cutting-edge technologies transforming the real of scientific calculators. The workshop was focused to equip participants with in-depth knowledge of advanced scientific calculator features. The primary goal was to empower participants to leverage smart calculators for enhanced problem-solving and efficiency, despite the enhanced understanding of advanced scientific calculator functionalities. In the era of digital transformation, calculators have evolved beyond basic arithmetic. The main problem related to students' difficulties in using scientific calculators is a combination of factors including a lack of understanding of calculator functions, challenges with inputting calculations correctly, confusion with the calculator interface, and insufficient instruction or practice. Therefore, Smart Calculator 3.0 workshop aimed to bridge the gap between traditional and advanced scientific calculator usage, and enthusiasts eager to harness the full potential of these devices. We hope this workshop can help students improve their proficiency with scientific calculators and ultimately enhance their academic performance. The workshop's primary objectives included introducing participants to advanced calculator functionalities, exploring realworld applications, and fostering a collaborative learning environment. The participants were from Pre-Diploma and Diploma students at UiTM Cawangan Negeri Sembilan, Kuala Pilah Campus.